The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s11230-021-09984-2
|View full text |Cite
|
Sign up to set email alerts
|

Sea lice (Copepoda: Caligidae) from South Africa, with descriptions of two new species of Caligus

Abstract: Thirteen species of sea lice (family Caligidae) are reported from a range of elasmobranch and actinopterygian fishes caught off South Africa or obtained from public aquaria in South Africa. Two new species of Caligus Müller, 1785 are described: C. linearisn. sp. from Pomatomus saltatrix (Linnaeus) and C. tumulusn. sp. from Chrysoblephus cristiceps (Valenciennes). A supplementary description is provided for both sexes of Caligus tetrodontis Barnard, 1948 taken from Amblyrhynchotes honckenii (Bloch) and previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Amplification reactions for each gene region were carried out in 25 µL volumes using: 12.5 µL of DreamTaq PCR Master Mix (2X) (ThermoFischer Scientific, Waltham, MA, USA), 1.25 µL of 10 µM of each primer, 3 µL of DNA product and 7 µL of double distilled water. Thermocycling conditions followed Song et al [85] for the 18S and 28S rRNA gene regions and Hayes et al [87] for the COI gene regions. Positive PCR products were verified by 1% agarose gel electrophoresis and sent to the commercial sequencing company Inqaba Biotechnical Industries (Pty) Ltd. (Pretoria, South Africa) for purification and sequencing in both directions.…”
Section: Molecular Analysismentioning
confidence: 99%
“…Amplification reactions for each gene region were carried out in 25 µL volumes using: 12.5 µL of DreamTaq PCR Master Mix (2X) (ThermoFischer Scientific, Waltham, MA, USA), 1.25 µL of 10 µM of each primer, 3 µL of DNA product and 7 µL of double distilled water. Thermocycling conditions followed Song et al [85] for the 18S and 28S rRNA gene regions and Hayes et al [87] for the COI gene regions. Positive PCR products were verified by 1% agarose gel electrophoresis and sent to the commercial sequencing company Inqaba Biotechnical Industries (Pty) Ltd. (Pretoria, South Africa) for purification and sequencing in both directions.…”
Section: Molecular Analysismentioning
confidence: 99%
“…This report highlighted the evidence of C. fugu in captive map puffer, which was caught in the Phuket Sea of Thailand, and characterized the parasites by the morphological observation under stereomicroscope. C. fugu was specified by a reduced leg 4 (Yamaguti, 1936;Ohtsuka et al, 2009;Venmathi Maran et al, 2011;Hayes et al, 2021). In addition, previous studies suggested that C. fugu seems to disappear from the Grass puffer (T. niphobles) in cold seasons (Venmathi Maran et al, 2011;Okawachi et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…The sample size given in brackets. c 1 El-Lamie and Abdel-Mawla (2012) ; 2 Özak et al (2012) ; 3 Jianying et al (2003) ; 4 Hung et al (2020) ; 5 Quilichini et al (2015) ; 6 Bray and Justine (2014) ; 7 Toman (1992) ; 8 Beveridge et al (2014) ; 9 Bakopoulos et al (2017) ; 10 Moravec and Justine (2008) ; 11 Moravec and Justine (2009) ; 12 Hayes et al (2021) ; 13 Justine (2010) . …”
Section: Introductionmentioning
confidence: 99%